A Sharia Economic Law Review of Profit-Sharing Practices - Sandi Wijaya; Zaenal Abidin; Reza Okva Marwendi; Ahmad Luthfi (Zabags International Journal of Islamic Studies, 2025)
This study examines profit-sharing practices at Koperasi Insan Madani Syariah in Rantau Karya Village and evaluates their conformity with Sharia economic law. Motivated by the need for equitable Islamic economic arrangements as alternatives to interest-based mechanisms, the research aims to identify how profit-sharing is operationalized and to assess its legal-normative alignment. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and document analysis involving cooperative managers, members, and community leaders. Findings indicate that the cooperative implements profit-sharing primarily through mudharabah mutlaqah and syirkah al-inan arrangements, distributing residual income proportionally based on members’ capital contributions and transactional participation; transparency and annual deliberations reinforce member trust, while gaps remain in members’ technical understanding of nisbah calculations. The study contributes theoretically by explicating how distributive justice principles under Sharia manifest in micro-cooperative settings and offers practical insights for improving governance, member education, and accountability in Sharia microfinance institutions. The results provide an empirical reference for practitioners and policymakers seeking to strengthen Sharia-compliant profit-sharing mechanisms at the grassroots level.